IMPLEMENTASI MODEL BLENDED LEARNING PADA MATA PELAJARAN IPS DI SD INPRES 12/79 MACANANG - Imran, Fitrya Ali; S, Syahriana (EDUCHILD (Journal of Early Childhood Education), 2022)
This paper discusses "Implementation of the Blended Learning Model in Social Studies Subjects at SD Inpres 12/79 Macanang". There are two sub-problems studied in this thesis, namely the implementation of the Blended Learning model in social studies subjects and the obstacles encountered in implementing the Blended Learning model in social studies subjects at SD Inpres 12/79 Macanang. To obtain answers to these problems, the authors used qualitative research with a type of phenomenology. The data collection techniques used were observation, interviews and documentation. Meanwhile, the data analysis technique used is data reduction, data display and conclusion drawing/verification. The research results show that; 1) the implementation of the Blended Learning model for social studies subjects at SD Inpres 12/79 Macanang is carried out in three stages, namely the planning stage, the implementation stage and the evaluation stage. 2) the obstacles encountered in implementing the Blended Learning model in social studies subjects at SD Inpres 12/79 Macanang, namely the use of internet data, sometimes there are students who cannot afford to buy internet data so that learning is carried out hampered and there are still students who do not have the the name is a cellphone or cell phone which is also an obstacle for students and educators in online learning. Meanwhile, in face-to-face learning, sometimes there are students who forget about health protocols, such as forgetting to wear masks.